Adrenomedullin Therapy for Moderate-to-Severe COVID-19 Pneumonia: Double-Blind Placebo-Controlled Phase 2a Trial - Toshihiro Kita; Norio Ohmagari; Sho Saito; Hiroshi Mukae; Takahiro Takazono; Taka-Aki Nakada; Tadanaga Shimada; Yuji Hirai; Yuichiro Shindo; Kosaku Komiya; Atsushi Saito; Masaya Yamato; et al. (Viruses)
Adrenomedullin (AM) is a bioactive peptide that is strongly induced during severe inflammation, including pneumonia and sepsis, and serves as an organ-protective factor. The plasma concentration of AM is markedly increased in the novel coronavirus disease COVID-19 and is closely related to the severity of the disease and prognosis of patients. We performed two investigator-initiated trials to evaluate the efficacy and safety of AM in patients with moderate-to-severe COVID-19. This multicenter, double-blind, placebo-controlled phase-2a trial evaluated COVID-19 patients with severe (n = 33) and moderate (n = 31) pneumonia in Japan. Patients were randomly assigned to receive either 15 ng/kg/min AM or placebo. The primary endpoint was the duration of mechanical ventilation (MV) for severe pneumonia and oxygen support for moderate pneumonia. The main secondary endpoint was clinical status up to 30 days after the intervention. No differences in primary or secondary endpoints were observed between the AM and placebo groups in patients with severe or moderate pneumonia. In the severe pneumonia group, three patients in the placebo group died due to respiratory failure, and one patient in the AM group died due to respiratory failure. The respiratory function test at 30 days in the moderate pneumonia group tended to be better than that in the AM group and approached significance (p = 0.073). Although mild adverse events caused by the vasodilatory effects of AM were noted, the safety of AM for treating pneumonia was confirmed. In these trials, we did not observe a definitive efficacy of AM in moderate to severe pneumonia. Alternative strategies for the treatment of AM in pneumonia require further research.